Simulation of an industrial trickle bed hydrogenation reactor in the pulsing flow regime. (2nd February 2010) - Cheng, Zhen-Min; Zhou, Zhi-Ming; Huang, Hua-Jiang; Yuan, Pei-Qing; , Dong Yang
An industrial trickle bed reactor was simulated for pyrolysis gasoline selective hydrogenation. The operation was recognised in the upper limit of pulsing flow regime by the Charpentier-Tosun flow pattern diagram at a very low hydrogen to oil volumetric ratio. Hydrodynamic parameters in the pulsing flow regime were calculated from the literature correlations which apply to the hydrogen-paraffin system. The external wetting efficiency which should be no higher than 100% was found to be 147% according to the correlation of Al-Dahhan and Dudukovic (1995), due to the undefined upper limit of their equation. The reactor simulation shows the gas-liquid and liquid-solid mass transfer rates were large enough for the active Pd hydrogenation catalyst. By comparing with the mass transfer rate in the Taylor flow regime in a monolithic structure, it shows the hydrogen concentration in the liquid phase in an industrial trickle reactor is more than two times of that in the monolith, which implies the substitution of the conventional catalyst pellet by the monolith is not required.